The role of β‐barrels 1 and 2 in the enzymatic activity of factor XIII A‐subunit. (27th May 2018) - Hethershaw, E. L.; Adamson, P. J.; Smith, K. A.; Goldsberry, W. N.; Pease, R. J.; Radford, S. E.; Grant, P. J.; Ariëns, R. A. S.; Maurer, M. C.; Philippou, H.
Abstract : Essentials The roles of β‐barrels 1 and 2 in factor XIII (FXIII) are currently unknown. FXIII truncations lacking β‐barrel 2, both β‐barrels, or full length FXIII, were made. Removing β‐barrel 2 caused total loss of activity, removing both β‐barrels returned 30% activity. β‐barrel 2 is necessary for exposure of the active site cysteine during activation. Summary: Background: Factor XIII is composed of an activation peptide segment, a β‐sandwich domain, a catalytic core, and, finally, β‐barrels 1 and 2. FXIII is activated following cleavage of its A‐subunits by thrombin. The resultant transglutaminase activity leads to increased resistance of fibrin clots to fibrinolysis. Objectives: To assess the functional roles of β‐barrels 1 and 2 in FXIII, we expressed and characterized the full‐length FXIII A‐subunit (FXIII‐A) and variants truncated to residue 628 (truncated to β‐barrel 1 [TB1]), residue 515 (truncated to catalytic core [TCC]), and residue 184 (truncated to β‐sandwich). Methods: Proteins were analyzed by gel electrophoresis, circular dichroism, fluorometric assays, and colorimetric activity assays, clot structure was analyzed by turbidity measurements and confocal microscopy, and clot formation was analyzed with a Chandler loop system. Results and Conclusions: Circular dichroism spectroscopy and tryptophan fluorometry indicated that full‐length FXIII‐A and the truncation variants TCC and TB1 retain their secondary and tertiary structure. Removal of β‐barrel 2 (TB1) resulted in total loss of transglutaminase activity, whereas the additional removal of β‐barrel 1 (TCC) restored enzymatic activity to 30% of that of full‐length FXIII‐A. These activity trends were observed with physiological substrates and smaller model substrates. Our data suggest that the β‐barrel 1 domain protects the active site cysteine in the FXIII protransglutaminase, whereas the β‐barrel 2 domain is necessary for exposure of the active site cysteine during activation. This study demonstrates the importance of individual β‐barrel domains in modulating access to the FXIII active site region.